Construction of Tudang Sipulung as A Group Counseling Strategy for Bugis Adolescents in The Perspective of KIPAS Counseling Model - Aswar, Aswar; Nur, Edil Wijaya; Amirullah, M.; Fitriana, Fitriana (Jurnal Kajian Bimbingan dan Konseling, 2022)
The purpose of this article is to describe the existence of Tudang Sipulung for group guidance that used KIPAS Counseling for the Bugis Youth at Senior High School at Sidrap. This research used a qualitative approach with Triple Hermeneutic Analysis method. The data collection technique are Interview and literature studies as well as data validation which is achieved through data triangulation. The subjects of this study were four people, two people from public figure (culturalists) and two people from students (Bugis youth). The results showed that Tudang Sipulung is the ancestral heritage of the Sidrap’s Bugis Society which contains positive values in the deliberation to reach consensus. In the practice of guidance and counseling, Tudang Sipulung can be constructed and implemented as group guidance in the perspective of the KIPAS counseling model in serving the counselee or Bugis Youth. The cultural values of Tudang Sipulung that can be integrated with the KIPAS model counseling include the counselor’s self-positioning, discussion themes, attitude, and positive thinking techniques, as well as the special technique of KIPAS is KaDo-MUDAH, and up to the steps of the KIPAS Counseling model